Development of an Organo-Mineral Fertiliser Based on Glauconite and Vermicompost - Makhanbetov, Arman; Yuldashbek, Davlat; Gaipov , Tulkinzhon; Adylov, Aidarbek (International Journal of Environmental Science and Green Technology, ISSN: 3080-8693, 2026)
This study presents the development of an organo-mineral fertiliser based on vermicompost and the natural aluminosilicate mineral glauconite, as well as the evaluation of its agrochemical properties. It was shown that vermicompost enhances soil biological activity and, through organic compounds and microbiological processes, accelerates the transformation of mineral components. Glauconite acts as a source of potassium and trace elements with prolonged release and, due to its high cation-exchange capacity, ensures their retention and gradual availability. Various component ratios (4:6-7:3) were investigated, and the optimal ratio was determined to be 6:4 (glauconite:vermicompost), providing a balanced proportion of organic and mineral constituents. The proposed production technology includes grinding the mineral raw material to a fraction of 0.1-1.0 mm, mixing the components, granulation with particle formation of 5-10 mm, and subsequent mild drying at 40-60 °C. This technological scheme ensures controlled and prolonged release of nutrients. It was established that the developed organo-mineral system improves soil moisture retention capacity, reduces nutrient losses due to leaching, and stabilises the plant's nutrient supply regime.